La incidencia de la estimulación temprana en el desarrollo de habilidades sociales en niños de 3 años en el CDI y escuela el saber es poder al sur de la ciudad de Guayaquil - Castro Mosquera, Evelyn Estefanía (2016)
The main objective of this thesis is the proposal of the Portage Guide for thedevelopment of social skills in children from 0 to 3 years in the CDI and School el Saberes Poder during the academic year 2016-2017. The research begins with the concept of early stimulation as it influences thedevelopment of social skills by making protagonism to different authors as vigostky inhis theory says that not only development affects learning but learning affects development of the child, it is by This we emphasize that observing the children of the CDI and Escuela el Saber es Poder are not being adequately stimulated…..